2011
DOI: 10.1208/s12249-011-9652-8
|View full text |Cite|
|
Sign up to set email alerts
|

The Stabilizing Effect of Moisture on the Solid-State Degradation of Gabapentin

Abstract: Abstract. Gabapentin is known to undergo intramolecular cyclization to form a lactam (gaba-L) with concomitant loss of water. Gabapentin was milled in a planetary mill for 15-60 min. Unmilled and milled gabapentin were stored at 50°C with relative humidity ranged between 5% and 90%. The unmilled and milled samples were assayed for gabapentin and gaba-L by reversed phase-high-performance liquid chromatography and also subjected to powder X-ray diffraction, solid-state nuclear magnetic resonance and surface area… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 12 publications
1
15
0
Order By: Relevance
“…Other research performed in the context of this project includes the work reported by Zong and coworkers (7). Additional reports are expected.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…Other research performed in the context of this project includes the work reported by Zong and coworkers (7). Additional reports are expected.…”
Section: Introductionmentioning
confidence: 82%
“…They milled form II for 15-60 min and stored the samples at 50°C, at relative humidity values ranging from 5% to 80%. The chemical instability, based on the amount of gabapentin lactam formed, was measured by reverse phase high-performance liquid chromatography (HPLC) (7). While milling did not cause any physical transformation, the amount of lactam formed increased with milling time.…”
Section: Introductionmentioning
confidence: 99%
“…Loss of the integrity of the drug molecule at any stage may alter their physicochemical properties and therefore impact clinical outcome. If chemically degraded to toxic product, it may harm the patients instead of benefitting them …”
Section: Introductionmentioning
confidence: 99%
“…If chemically degraded to toxic product, it may harm the patients instead of benefitting them. 6 Warfarin sodium, an anticoagulant drug, has been widely used to treat various cardiovascular conditions and prevent clotting after medical intervention. 7 International normalized ratio (INR), which represents the effectiveness of the anticoagulant, is frequently monitored for patients on warfarin therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Various polymorphs, amorphous, hydrates, and solvates will have an impact on the physicochemical and mechanical properties of a drug substance. During manufacturing processes, there are many factors which will affect the solid-state characteristics of a drug such as temperature, light, humidity, pressure, processing time, and solvents (3)(4)(5). These factors will not only influence the physicochemical properties of the drug, but also on their efficacy (6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%